A Rare Presentation of Maydl’s Hernia - Elroy Patrick Weledji; Martin Mokake; Marcelin Ngowe Ngowe (Case Reports in Surgery)
We present a case of an unsual type of obstructed indirect inguinal hernia with impending strangulation. The operative findings revealed a sliding Maydl’s hernia with an ischemic inner ileal loop and an adherent inflamed appendix. This case highlights the importance of intraoperative examination of the intra-abdominal bowel loops proximal to the hernia sac of an incarcerated, obstructed, or strangulated hernia.